NGO–researcher partnerships in global health research: benefits, challenges, and approaches that promote success. Issue 4 (18th May 2016) - Olivier, Catherine; Hunt, Matthew R.; Ridde, Valéry
ABSTRACT: Partnerships involving NGOs and academic researchers (NGO–R partnerships) are increasing in global health research. Such collaborations present opportunities for knowledge translation in global health, yet are also associated with challenges for establishing and sustaining effective and respectful partnerships. We conducted a narrative review of the literature to identify benefits and challenges associated with NGO–R partnerships, as well as approaches that promote successful partnerships. We illustrate this analysis with examples from our own experiences. The results suggest that collaborations characterised by trust, transparency, respect, solidarity, and mutuality contribute to the development of successful and sustainable NGO–R partnerships.